Functional Delivery of a Membrane Protein into Oocyte Membranes Using Bicelles, - Kang, Congbao (2010)
The voltage-gated potassium channel modulatory membrane protein KCNE3 was overexpressed and purified into both micelles and bicelles. Remarkably, microinjection of KCNE3 in bicelles into Xenopus oocytes resulted in functional co-assembly with the human KCNQ1 channel expressed therein. Microinjection of LMPC micelles containing KCNE3 did not result in channel modulation, indicating that bicelles sometimes succeed at delivering a membrane protein into a cellular membrane when classical micelles fail. Backbone NMR resonance assignments were completed for KCNE3 in both bicelles and LMPC, indicating that the secondary structure distribution in KCNE3’s N-terminus and transmembrane domains exhibits only modest differences from that of KCNE1, even though these KCNE family members have very different affects on KCNQ1 channel function.